Factors Associated with Housekeeping Implementation Behavior in The Production Department at PT. X, Batam City, in 2024 - Amaliah, Rizqi Ulla; Utami, Leni; Sundari, Agung; Albati, Muhammad (Rifa'Institute, 2025)
Introduction: Housekeeping is a fundamental aspect of Occupational Safety and Health, contributing to improved workplace organization, reduced hazards, and enhanced productivity. Effective housekeeping implementation is influenced by multiple factors, including supervisory oversight and the availability of adequate facilities. Objective: This study aimed to determine the relationship between supervision and facility availability with housekeeping implementation behavior among production workers at PT X, Batam City. Method: A quantitative research design with a cross-sectional approach was employed, and data collection was conducted from May to June 2024. The study population comprised 150 production workers, with a sample size of 109 respondents determined using Slovin’s formula. A simple random sampling technique was applied. Research instruments included questionnaires, interviews, mobile devices, observation sheets, and documentation tools. The Chi-square test was used for statistical analysis. Result and Discussion: The results showed a significant relationship between supervision and housekeeping behavior (p = 0.001) as well as between facility availability and housekeeping behavior (p < 0.001). These findings indicate that both adequate supervision and sufficient facility provision play a crucial role in promoting effective housekeeping practices in the production area. Conclusion: The study concludes that strengthening supervisory roles and improving facility availability are essential strategies for enhancing occupational safety and housekeeping behavior among industrial workers.